Evaluation of titanium oxide introduction in the electrode structure for portable PEMFC applications. (5th August 2021) - Gatto, I.; Saccà, A.; Pedicini, R.; Passalacqua, E.; Carbone, A.
Abstract: Polymer electrolyte membrane fuel cells (PEMFCs) are among the best candidates to power a variety of devices, especially for portable applications. In the latter case, restrictive operating conditions, such as low pressure and humidity, impose particular requirements for such systems. Hence, the optimization of the electrodes in order to operate in such harsh conditions is necessary. In this work, the influence of introducing titanium oxide (TiO2 ) in the catalytic layer on the MEA performance was evaluated. TiO2 was selected since it can act both as a mechanical reinforcement for the catalyst support, and as a catalyst for the decomposition of hydrogen peroxides, forming during the fuel cell operations. Composite electrodes containing different loadings of TiO2 were developed, using 0.3 and 0.6 mg cm −2 of Pt at the anode and cathode, respectively. Electrochemical studies, in terms of I–V curves, cyclic voltammetry and accelerated stress tests (ASTs), were carried out in a 25 cm 2 single cell. It was found that an addition of a 12 wt% of TiO2 produced an 8% of ECSA reduction after the Accelerated Stress Tests (ASTs) compared to the 25% reduction displayed by the membrane-electrode assembly (MEA) equipped with bare Pt/C. Highlights: Evaluation of the optimal amount of TiO2 in the catalytic layer. TiO2 introduction in CL reduces the catalyst degradation due to carbon corrosion. AST on 12TiO2 PtC MEA highlighted a lower ECSA reduction respect to reference MEA.